1983
DOI: 10.1080/10862968309547486
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inference Training on Children's Comprehension of Expository Text

Abstract: Abstract. Three procedures were used to help sixth-grade children increase inferential reading comprehension with expository text: a structured overview to activate background knowledge, the cloze procedure to develop an inferential thinking strategy, and a self-monitoring checklist to train the subjects to use the strategy independently. There were two treatment groups. One used the cloze procedure to integrate text and background knowledge and the checklist to maintain the strategy; the other used both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Participants in the treatment group of the present study scored significantly higher on the Inference subtest of the WGCTA than the control group, which is consistent with previous research, suggesting the utility of explicit strategy instruction (Fisher et al, 2002;Lenz & Hughes, 1990;Schumaker & Deshler, 1992;Seybert, 1998). This result was consistent with several studies investigating explicit instruction in inference generation, which showed positive and significant results favoring the treatment group on reading comprehension measures (Carnine, Kameenui, & Woolfson 1982;Carr, Dewitz, & Patberg, 1983;Dewitz et al, 1987;Flores & Ganz, 2007, 2009O'Connor & Klein, 2004;Reutzel & Hollingsworth, 1988). However, no significant differences were found between the groups for generating inferences in reading on the IGIRT.…”
Section: Reading Inference Generationsupporting
confidence: 94%
“…Participants in the treatment group of the present study scored significantly higher on the Inference subtest of the WGCTA than the control group, which is consistent with previous research, suggesting the utility of explicit strategy instruction (Fisher et al, 2002;Lenz & Hughes, 1990;Schumaker & Deshler, 1992;Seybert, 1998). This result was consistent with several studies investigating explicit instruction in inference generation, which showed positive and significant results favoring the treatment group on reading comprehension measures (Carnine, Kameenui, & Woolfson 1982;Carr, Dewitz, & Patberg, 1983;Dewitz et al, 1987;Flores & Ganz, 2007, 2009O'Connor & Klein, 2004;Reutzel & Hollingsworth, 1988). However, no significant differences were found between the groups for generating inferences in reading on the IGIRT.…”
Section: Reading Inference Generationsupporting
confidence: 94%
“…Some of the studies were found in multiple reports. Many of the duplicated studies were published from dissertations (e.g., Carr, Dewitz, & Patberg, 1983; Hansen, 1981; Hansen & Pearson, 1983), or were research findings summarized in teacher journals or book chapters (e.g., Holmes, 1983; Yuill & Oakhill, 1991). If two reports were found for the same experiments, the earlier report was coded.…”
Section: Methodsmentioning
confidence: 99%
“…The basic result was that students learned to comprehend and acquire the kind of information from new stories, presented without any adjunct questions, that was required in the training stories. Carr, Dewitz, and Patberg (1983) employed three types of training with sixth graders: a structured overview to activate background knowledge, a cloze procedure designed to develop inferencing, and a self-monitoring checklist. One training group used the cloze procedure and the checklist, the second used the overview and cloze procedures.…”
Section: Instruction In Reading Comprehension Skillsmentioning
confidence: 99%